Clinical relevance of echocardiogram in patients with cerebral palsy undergoing posterior spinal fusion. Issue 8 (9th May 2015) - DiCindio, Sabina; Arai, Lynda; McCulloch, Michael; Sadacharam, Kesavan; Shah, Suken A.; Gabos, Peter; Dabney, Kirk; Theroux, Mary C.; Davidson, Andrew
Summary Background Spinal deformity is one of the secondary musculoskeletal problems that occur with cerebral palsy (CP). Of the co morbidities associated with CP and spinal deformity, cardiac function is of theoretical concern. Objective The goal of our study was to determine the clinical relevance of routine preoperative cardiology evaluation via echocardiogram for patients with CP presenting for posterior spine fusion (PSF) surgery. Methods A retrospective chart review was performed of CP patients presenting for scoliosis surgery. The data collected for each patient included: age, sex, height, weight, Cobb angle, and medical history. All patients had a preoperative cardiac evaluation. Results Seventy‐two patients were included. The mean age was 13.6 ± 3.4 years. Left ventricular systolic function was normal in all patients; the mean shortening fraction was 39.3 ± 6.2%. No patient had more than mild insufficiency of either the semilunar or atrioventricular valve. One patient was diagnosed with aortic root dilation as well as aortic valve insufficiency. All patients had PSF surgery without changes in anesthetic or surgical plans, and no patient experienced complications attributable to a cardiac origin. Conclusion The results suggest that routine preoperative cardiology evaluation via echocardiogram for children with CP in the absence of clinical history or physical examination findings suggestive of cardiac disease is not necessary.